2022
DOI: 10.3390/antiox11091697
|View full text |Cite
|
Sign up to set email alerts
|

Olanzapine Ameliorates Ischemic Stroke-like Pathology in Gerbils and H2O2-Induced Neurotoxicity in SH-SY5Y Cells via Inhibiting the MAPK Signaling Pathway

Abstract: Olanzapine (OLNZ) is used to treat psychotic disorders. To look into the neurological basis of this phenomenon, we investigated the neuroprotective effects of OLNZ in gerbils and SH-SY5Y cells. Gerbils were subjected to transient global cerebral ischemia (TGCI) by blocking both common carotid arteries, and OLNZ (10 mg/kg) was injected intraperitoneally. Hydrogen peroxide (H2O2) was used to induce oxidative-stress-mediated damage in the SH-SY5Y cells. The results indicated that OLNZ administration markedly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…The mitogen-activated protein kinase (MAPK)-activated protein kinase 5 (APK5), a member of the serine/threonine kinase family, is activated by cellular stress and proinflammatory cytokines [ 35 ]. The MAPKAPK5 Antisense RNA 1 (MAPKAPK5-AS1) prevents MAPKAPK5 from being translated into a protein and recent study showed that IS-like pathology was ameliorated by inhibiting the MAPK signaling pathway [ 36 ]. Lastly, we performed PWAS fine-mapping to identify protein levels causally relevant to IS risk.…”
Section: Resultsmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK)-activated protein kinase 5 (APK5), a member of the serine/threonine kinase family, is activated by cellular stress and proinflammatory cytokines [ 35 ]. The MAPKAPK5 Antisense RNA 1 (MAPKAPK5-AS1) prevents MAPKAPK5 from being translated into a protein and recent study showed that IS-like pathology was ameliorated by inhibiting the MAPK signaling pathway [ 36 ]. Lastly, we performed PWAS fine-mapping to identify protein levels causally relevant to IS risk.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the MAPK signaling pathway is closely related to inflammation-mediated ischemic injury [24]. The MAPK signaling pathway inhibition can inhibit neuronal apoptosis and inflammatory response, protect damaged brain tissue, and improve nerve injury [25]. Many studies have also shown that PI3K/Akt signaling pathway is essential in the pathogenesis of ischemic stroke and plays a vital role in the anti-apoptosis of nerve cells, oxidative stress, inflammation, inflammation, and inflammation autophagy [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen-activated protein kinase (MAPK)-activated protein kinase 5 (APK5), a member of the serine/threonine kinase family, is activated by cellular stress and proinflammatory cytokines [51]. The MAPKAPK5 Antisense RNA 1 (MAPKAPK5-AS1) prevents MAPKAPK5 from being translated into a protein and recent study showed that IS-like pathology was ameliorated by inhibiting the MAPK signaling pathway [52]. Lastly, we performed PWAS finemapping to identify protein levels causally relevant to IS risk.…”
Section: Fine-mapping Analysis Identifies 9 Causal Genes/proteins For...mentioning
confidence: 99%